2016
DOI: 10.1080/13668803.2016.1227770
|View full text |Cite
|
Sign up to set email alerts
|

The influence of motherhood on income: do partner characteristics and parity matter?

Abstract: Although the economic independence of women has been greatly advanced in recent decades, it continues to lag far behind men's in the Netherlands and elsewhere. The negative consequences of motherhood are an important driving force behind women's abiding lower income. Although mother's lower earnings have received a substantial amount of attention from scholars and the underlying mechanisms are well established, surprisingly little is known about mitigating factors. This article contributes to the literature by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…The pivotal transition theory has received more empirical support in studies outside the U.S. Hsu (2021), for example, found that in Japan, a woman's first birth, rather than the second, leads to a larger and more persistent earnings penalty. Other studies have also shown that compared to subsequent births, the first child is associated with a larger penalty in earnings in Norway (de Hoon et al 2017) and a larger penalty in occupational status in other European countries (Abendroth et al 2014). In line with these studies, I hypothesize the following: The motherhood penalty in authority will be larger for the first child than for subsequent children (Hypothesis 2a).…”
Section: Motherhood and Birth Paritymentioning
confidence: 65%
See 1 more Smart Citation
“…The pivotal transition theory has received more empirical support in studies outside the U.S. Hsu (2021), for example, found that in Japan, a woman's first birth, rather than the second, leads to a larger and more persistent earnings penalty. Other studies have also shown that compared to subsequent births, the first child is associated with a larger penalty in earnings in Norway (de Hoon et al 2017) and a larger penalty in occupational status in other European countries (Abendroth et al 2014). In line with these studies, I hypothesize the following: The motherhood penalty in authority will be larger for the first child than for subsequent children (Hypothesis 2a).…”
Section: Motherhood and Birth Paritymentioning
confidence: 65%
“…Other studies have also shown that compared to subsequent births, the first child is associated with a larger penalty in earnings in Norway (de Hoon et al. 2017) and a larger penalty in occupational status in other European countries (Abendroth et al. 2014).…”
Section: Introductionmentioning
confidence: 96%
“…However, in the latter study, being single was found to be associated with maternal death. This difference may be due to single and highly educated women earning more than their married counterparts [19]. This associated increase in wealth may have attributed to quality obstetric care and being well-informed [18,20].…”
Section: Discussionmentioning
confidence: 99%
“…Y a mayor edad de las mujeres, la penalidad salarial por maternidad disminuye, pero influye el nivel de escolaridad. Por otro lado, el tema de los cuidados en ocasiones conlleva que las horas que destinan los hombres al trabajo doméstico, a pesar de que estas vayan en aumento, no tienen implicaciones directas en los ingresos de las mujeres, ya que ellos evitan actividades que incluyan el cuidado de los niños (Gash, 2009;Felfe, 2012;Staff y Mortimer, 2012;Gamboa y Zuluaga, 2013;Viitanen, 2014;De-Hoon et al, 2017;Li, 2017;Morgenroth y Heilman, 2017).…”
Section: Introductionunclassified